Contraction of fully expanded FMR1 alleles to the normal range: predisposing haplotype or rare events? - Maia, N (2017)
Fragile X syndrome (FXS), the most common cause of inherited intellectual disability, is due to the expansion over 200 CGGs and methylation of this polymorphic region, in the 5'-UTR (untranslated region) of FMR1 (Xq27.3). We have identified four FXS mosaic males: M1-(CGG)35/(CGG)>200; M2-(CGG)26/(CGG)>200; M3-(CGG)39/(CGG)>200; and M4-(CGG)18/(CGG)125/(CGG)>200. After genotyping their respective mothers, we suggested that normal alleles of these patients resulted from post-zygotic contractions of full expansions. The detection of these four rare independent cases led us to hypothesize the existence of a large-contraction predisposing haplotype in our population. Next, we questioned whether other normal pure CGGs would have arisen through similar contractions from fully expanded alleles. To address these questions, we identified stable single-nucleotide polymorphism (SNP) lineages and related short tandem repeat (STR) haplotypes (DXS998-DXS548-FRAXAC1-FRAXAC2) of the four mosaics, 123 unrelated FXS patients and 212 controls. An extended flanking haplotype (34-44-38-336) shared by mosaics from lineage A suggested a risk lineage-specific haplotype more prone to large contractions. Other normal pure FMR1 alleles from this SNP background also shared phylogenetically close STR haplotypes, although a single (CGG)exp>(CGG)24 contraction or the loss of AGG interruptions may explain their origin. In both scenarios, multistep FMR1 mutations involving the gain or loss of several CGGs seem to underlie the evolution of the repeat.